2019
DOI: 10.5114/pq.2019.84270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antenatal exercise on mode of delivery in gestational diabetic females: a single-blind randomized controlled trial

Abstract: Introduction. Gestational diabetes mellitus (GdM) is common in pregnancy. Maternal consequences might include an increased rate of caesarean delivery. This study was conducted to determine the effect of an exercise program on the mode of delivery in gestational diabetic females. Methods. A prospective, randomized, single-blind, pre-post-test, controlled trial was performed. overall, 60 pregnant females with GdM were included, at their 20-24 weeks of gestation, aged 25-35 years, with body mass index not exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Six papers reported rate of Caesarean section (CS) as an outcome. There was a significant difference in Awad’s [ 48 ] paper: the rate of CS was higher in the control group (63.4% ( n = 19/30) compared with 16% ( n = 5/30) in the exercise group, ( p = 0.001) . Five studies showed no difference in CS rates between the exercise intervention and control groups [ 35 , 37 , 39 , 47 ].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Six papers reported rate of Caesarean section (CS) as an outcome. There was a significant difference in Awad’s [ 48 ] paper: the rate of CS was higher in the control group (63.4% ( n = 19/30) compared with 16% ( n = 5/30) in the exercise group, ( p = 0.001) . Five studies showed no difference in CS rates between the exercise intervention and control groups [ 35 , 37 , 39 , 47 ].…”
Section: Resultsmentioning
confidence: 91%
“…Flow of studies through the stages of identification, screening, eligibility, and final inclusion is shown in Figure 1 . Fourteen randomised controlled studies were selected for inclusion in this systematic review [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Two of the papers [ 41 , 47 ] reported different outcomes from one trial and for the purpose of this manuscript are referred to as one paper.…”
Section: Resultsmentioning
confidence: 99%
“…The result of the study was in our support. [10] Gehan et al checked the e cacy of antenatal exercises on the mode of delivery and APGAR score in primigravida. They concluded that there was no relation between antenatal exercises and mode of delivery in primigravida.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation formula was N= (Z1-β + Z1 -α/2) 2(δ2 1 + δ2 2)/(µ1-µ2) /2,where desired Z1-α/2 Level of signi cance = 95% ,µ1 Expected mean change in APGAR scale in Control Group = 8.7 ,µ2 Expected mean change in APGAR scale in Experimental Group = 8.03,δ1 Expected standard deviation in Control group = 0.5,δ2 Expected standard deviation in Experimental group = 1.2,Z1-β power of the study = 80%. [10] Sample size in each group was 36.…”
Section: Sample Size Collectionmentioning
confidence: 99%
“…Compared with delivery by caesarean section (CS), the morbidity rate of mothers after vaginal delivery (Vd) is less, and their recovery period is shorter [8]. Physical activity is recommended for pregnant women because it plays an important role in reducing a potential risk of instrumental childbirth and CS [9]. delivery by CS generally decreases damages to the pelvic floor muscles (affecting urinary incontinence) but it damages abdominal muscles and can cause intestinal obstruction, chronic pelvic girdle pain, infertility, or difficulties due to repeated surgery.…”
Section: Introductionmentioning
confidence: 99%